Analysis of the Expression and Function of Immunoglobulin-Like Transcript 4 (ILT4, LILRB2) in Dendritic Cells from Patients with Systemic Lupus Erythematosus - Paola del Carmen Guerra-de Blas; Yael Sebastián Villaseñor-Talavera; Daniela de Jesús Cruz-González; Lourdes Baranda; Lesly Doníz-Padilla; Carlos Abud-Mendoza; Roberto González-Amaro; Adriana Elizabeth Monsiváis-Urenda (Journal of Immunology Research)
Dendritic cells (DC) play an important role in the development and maintenance of immune tolerance. Although the inhibitory receptor ILT4/LILRB2 has been related with the tolerogenic phenotype of DC, the possible role of this receptor in the breakdown of DC tolerogenic function in systemic lupus erythematosus (SLE) has not been elucidated. In this study, we analyzed the expression and function of the inhibitory receptor ILT4 in DC from SLE patients. We found that the percentage of ILT4 positive plasmacytoid DC and myeloid DC is significantly diminished in SLE patients. Interestingly, ligation of ILT4 did not affect the maturation or immunogenic capability of DC in healthy controls. In contrast, in SLE patients we observed an inhibitory effect of ILT4 on the immunogenic capability of DC. ILT4 was shown not to have a crucial role in regulating the maturation and function of DC from healthy controls but is partially involved in the maturation process and immunogenic capability of DC from SLE patients, suggesting that other inhibitory receptors, involved in the regulation of DC tolerogenic function, may be impaired in this autoimmune disease.